Sheehan Syndrome Presenting with Psychotic Manifestations Mimicking Schizophrenia in a Young Female: A Case Report and Review of the Literature - Nipun Lakshitha de Silva; Janith Galhenage; Madhubhashinee Dayabandara; Noel Somasundaram (Case Reports in Endocrinology)
Introduction. Sheehan syndrome presents with features of multiple hormone deficiencies including lactation failure and amenorrhoea as well as with features of central hypothyroidism and adrenocorticotropic hormone deficiency. Psychiatric manifestations are mostly limited to cognitive impairment. Psychotic presentations are rare and limited to case reports. Case Presentation. A 32-year-old female was evaluated for fearfulness and delusions for one year. She had persecutory and bizarre delusions, delusion of thought possession, and elementary auditory hallucinations. These began four months after the birth of her third child. The delivery had been complicated with postpartum haemorrhage. Her symptoms caused the functional decline and progressively worsened, resulting in suicidal ideation. Cognitive assessment revealed mild impairment in attention. Further inquiry revealed lethargy, constipation, cold intolerance, and lactation failure. She was slow, having dry skin, puffy face, and bradycardia with a blood pressure of 80/60 mmHg (supine) and 70/50 mmHg (standing). She had hyponatraemia, elevated creatine phosphokinase, low thyroxine, prolactin, FSH, LH, and IGF-1. She had poor cortisol and growth hormone response to the insulin tolerance test. MRI-pituitary showed empty sella. A diagnosis of Sheehan syndrome was made. Her symptoms improved completely after the initiation of levothyroxine and hydrocortisone. Conclusions. Sheehan syndrome can present with psychotic symptoms mimicking schizophrenia with variable involvement of cognition. Detailed reporting of these patients would enhance better characterization of the clinical presentation and risk profile of these patients.